Manajemen Human Capital dalam Meningkatkan Mutu Sekolah di SDIT Baiturrahim - Simbolon, Ali Mustopa Yakub; Junaidi, Junaidi; Hanani, Silfia; Sumarni, Weni; Bashori, Bashori; Fadilah, Rahmi (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The aim of this research is to determine human capital management in improving school quality at SDIT Baiturrahim. The research method used is descriptive qualitative with data collection techniques from observation, interviews and documentation. The subjects in this research were school principals, administrative employees and teachers. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The results of this research indicate that human capital management in improving (planning, organizing, actuating dan controlling) the quality of schools at SDIT Baiturrahim has generally been implemented. It can be seen from the various achievements that have been achieved by students and educators in various competitions ranging from city to provincial level. So that by obtaining these achievements, the quality of education at SDIT Baiturrahim can be improved.